A Qualitative Study of Perceptions About Voluntary Blood Donation Among the Supportive Service Employees of a Multispecialty Rural Tertiary Care Hospital - Antani , Dhara; Kumar, Dinesh (National Journal of Community Medicine, 2012)
Background The non-medical staff are involved in considerable interaction with the patients and their caretakers, in some instances more than physicians themselves. They are looked upon by the community as a source of knowledge and motivation for various health related matters. The effect of attitudes, norms and perceptions of support staff on community motivation various issues including blood donation is not widely studied. Objective To find the perception and views of this group of hospital staff about blood donation are also scarce. Methods A volunteer group of 23 non-medical hospital staff were studied using the ‘Free listing’ technique. Of these 7 most expressive participants were selected for ‘Pile Sorting’ exercise. Data was analyzed using Visual Anthropac, version 1.0 software. Result Of 119 responses listed, 15 commonest responses were used for pile sorting exercise. These then sorted into 5 clusters based on the perceptions of the respondents. The respondents were able to identify the domains with their thought process. Majority of the respondents believed that blood donation was mostly considered as a noble and life saving act. It was observed that there were several misconceptions regarding blood donation. The group also agreed to these misconceptions. Conclusion Such exercises help us to understand the different aspects of a topic (blood donation) as perceived by the target group. Such an understanding is vital to design any education programme for the group. Such studies help in providing the basis to for more representative quantitative studies.